Spatial Analysis of Soil Available Potassium and Plant Brix Content for Site Specific Nutrient Management in Sugarcane - Yagus Wijayanto; Moch. Reza Wahyu Abdilah; Ika Purnamasari; Tri Wahyu Saputra (AGRIVITA, Journal of Agricultural Science, 2022)
There has been a tendency of decreasing sugarcane productivity (Saccharum officinarum Linn) in Indonesia due to poor soil available potassium. There has also been evidence that available soil potassium relates directly to soil condition. For this reason, the management of sugarcane engaging Site Specific Nutrient Management (SSNM) must be pursued. The first and most important stage in SSNM is assessing variability, which can be used to recommend particular fertilizer. This research’s main aim is to assess the variability of Potassium and Brix content for uses in the Potassium (K) fertilizer recommendation. The methodology used in this research is collecting data in the field, analyzing with Geographical Information Systems (GIS) using Kriging techniques, and developing a site-specific K prescription map. The results show that (1) spatial analysis assisted in developing a prescription map for K management in sugarcane; (2) spatially, the area can be classified into three classes (low, medium, and high) of K with the recommendation of 300 kg/ha (low), 200 kg/ha (medium) and 0 kg/ha (high) respectively. The results suggest that spatial analysis of soil available potassium and Brix content can provide a whole and specific picture of the area studied, which is beneficial for SSNM.